Multi-Target Directed Donepezil-Like Ligands for Alzheimer's Disease - Unzeta, Mercedes; Esteban, Gerard; Bolea, Irene; Fogel, Wieslawa A.; Ramsay, Rona R.; Youdim, Moussa B. H.; Tipton, Keith F.; Marco-Contelles, José (Frontiers in Neuroscience, 2016)
Alzheimer's disease (AD), the most common form of adult onset dementia, is an age-related neurodegenerative disorder characterized by progressive memory loss, decline in language skills and other cognitive impairments. Although its etiology is not completely known, several factors including deficits of acetylcholine, β-amyloid deposits, τ-protein phosphorylation, oxidative stress and neuroinflammation are considered to play significant roles in the pathophysiology of this disease. For a long time, AD patients have been treated with acetylcholinesterase inhibitors such as donepezil (Aricept®) but with limited therapeutic success. This might be due to the complex multifactorial nature of AD, a fact that has prompted the design of new Multi-Target-Directed Ligands (MTDL) based on the “one molecule, multiple targets” paradigm. Thus, in this context, different series of novel multifunctional molecules with antioxidant, anti-amyloid, anti-inflammatory and metal-chelating properties able to interact with multiple enzymes of therapeutic interest in AD pathology including acetylcholinesterase, butyrylcholinesterase and monoamine oxidases A and B have been designed and assessed biologically. This review describes the multiple targets, the design rationale and an in-house MTDL library, bearing the N-benzylpiperidine motif present in donepezil, linked to different heterocyclic ring systems (indole, pyridine or 8-hydroxyquinoline) with special emphasis on compound ASS234, an N-propargylindole derivative. The description of the in vitro biological properties of the compounds and discussion of the corresponding structure-activity-relationships allows us to highlight new issues for the identification of more efficient MTDL for use in AD therapy.